1998
DOI: 10.1080/106351598260761
|View full text |Cite
|
Sign up to set email alerts
|

Reassessment of Homology of Morphological Characters in Tetractinellid Sponges Based on Molecular Data

Abstract: In sponges, as in other taxa with simple organization, the evaluation and use of morphological characters is difficult. Phylogenetic analysis of the first 850 nucleotides from the 5' end of the 28S rRNA gene is used here to assess the homology of spicules used in the classification of the subclass Tetractinellida. A single well-supported MP tree was obtained. The monophyly of the nine Tetractinellida species studied confirms the tetraxon megasclere as a morphological synapomorphy for the Tetractinellida. Two s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
103
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(110 citation statements)
references
References 20 publications
4
103
1
Order By: Relevance
“…Early molecular studies of the Astrophorida (Chombard et al 1998), based on 28S rDNA genes, indicated that although streptasters appeared early within the Astrophorida, they were lost subsequently in higher groups on the tree, such as the Geodiidae and Calthropellidae. Although branch support for deeper relationships is limited, our phylogenetic trees are in contrast with that presented by Chombard et al (1998), indicating that clades bearing streptasters (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Early molecular studies of the Astrophorida (Chombard et al 1998), based on 28S rDNA genes, indicated that although streptasters appeared early within the Astrophorida, they were lost subsequently in higher groups on the tree, such as the Geodiidae and Calthropellidae. Although branch support for deeper relationships is limited, our phylogenetic trees are in contrast with that presented by Chombard et al (1998), indicating that clades bearing streptasters (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…DNA of two specimens (SNSB-BSPG GW3934 and SNSB-BSPG GW4029) was extracted with the NucleoSpin Tissue kit (Macherey-Nagel); extracted DNA was quantified using a nanodrop. About 1 ng of genomic DNA was used as template in 25 µl reaction-mixes to amplify the C-region of the 28S ribosomal RNA (rRNA) gene by PCR with the following primers: fwd: 5'-GAAAAGAACTTTGRARAGAGAGT-3' and rv: 5'-TCCGTGTTTCAAGACGGG-3' (Chombard et al 1998) Alignment and phylogenetic analysis. The sequences of L. translucida sp.…”
Section: Methodsmentioning
confidence: 99%
“…For the 28S fragment the primers 28S-C2-fwd (GAA AAG AAC TTT GRA RAG AGA GT) and 28S-D2-rev (TCC GTG TTT CAA GAC GGG) were used (Chombard et al, 1998). The 25 µL PCR mix consisted of 5 µL 5x green GoTaq ® PCR Buffer (Promega Corp, Madison, WI), 4µL 25mM MgCl2 (Promega Corp, Madison, WI), 2 µL 10mM dNTPs, 2 µL BSA (100µg/ml), 1 µL each primer (5µM), 7.8 µL water, 0.2µL GoTaq® DNA polymerase (5u/μl) (Promega Corp, Madison, WI) and 2 µL DNA template.…”
Section: Demosponge Samplesmentioning
confidence: 99%
“…This marker shows considerable phylogenetic signal on lower taxonomic levels (e.g., Chombard et al, 1998;Erpenbeck et al, 2007a;Cardenas et al, 2009;Schuster et al, 2015) and has also been successfully applied for the molecular taxonomy of Calcarea (Voigt and Wörheide, 2016).…”
Section: Introductionmentioning
confidence: 99%